Remittances, rituals and reconsidering women's norms in mahallas: emigrant labour and its social effects in Ferghana Valley. Issue 1 (2nd January 2016) - Kikuta, Haruka
Abstract : This paper describes recent economic and social changes in Central Asian neighbourhood communities known as mahalla s, using data from a town in Ferghana Valley. First, it examines how the increasing costs of life-cycle rituals are damaging the harmony of mahalla s. Since 2007, more and more hosts have begun to outsource the provision of food and services for these rituals, using money acquired mostly through emigrant labour. This in turn lessens mahalla s' mutual aid practices, and reveals emerging economic disparities between neighbours. Secondly, the paper argues that emigration has had transformative effects on the lifestyles of Muslim women in mahalla s. With the globalization of their economy, conventional local norms are becoming harder to obey, and some young and middle-aged women are choosing to live outside these norms. Dependence on emigrant labour and the associated remittances has significantly affected the lifestyles and morals of mahalla inhabitants.